Mobilizing Civil Society to Fight Corruption in Bangladesh - Landell-Mills, Pierre (World Bank, Washington, DC, 2012)
A successful anti-corruption strategy must have a free press to voice public opinion and report cases of corruption, an effective and politically neutral mechanism to investigate and prosecute corruption, and a reliable judicial process to punish wrongdoing when it is proved. It is rare to find all these elements in a developing country. without considerable public pressure, governments are unlikely to foster the transparency and accountability needed to curb malfeasance by public officials. Consequently there is a major role for civil society organizations to campaign for such reforms. This is the mission of the national chapters of Transparency International. This Note discusses the crucial role played by the Bangladesh chapter of Transparency International in pressing for the implementation of corruption reform, publicizing well-researched facts about corruption, and lobbying for additional measures.